Hierarki Pengaruh Terhadap Kebijakan Redaksi: Studi Kasus di TV one dan Metro TV dalam Pemberitaan Pilpres 2024 - Maria Ulfah; Zaeni Rokhi; Gun Gun Heryanto; Tantan Hermansah; Muhammad Fanshoby (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The relationship between television media tvOne and Metro TV and politics is a dilemmatic one, this can give rise to the attitude of each media in reporting the 2024 presidential election. A reality in a political moment is never completely neutral from political interpretation or capital patronage. In this case, the media is expected to be a watchdog in an ideal democratic system, but this cannot be realized according to its expectations. The aim of this research is to find out what the hierarchy of influence is in the editorial policies of tvOne and Metro TV in reporting on the 2024 presidential election. And what the hierarchical comparison looks like influence in editorial policy on reporting on the 2024 presidential election on tvone and metro tv. The research method used is qualitative, with a case study approach. In this research, the paradigm used is the critical paradigm. Data sources come from in-depth observations, interviews with tvOne News Anchor, Metro TV Senior Journalist and Senior Producer, and documentation regarding the 2024 presidential election on the tvOne and Metro TV YouTube channels. Of the five levels, namely Individual Level, Routine Level, Organizational Level, Extra Media Level and Ideology Level. The significant influence of these five levels is the Ideology Level, at this level the values ​​that are firmly held by tvOne and Metro TV in their reporting, including reporting on the 2024 Presidential Election.